2008
DOI: 10.2166/wp.2008.208
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-hegemony in the Amu Darya Basin

Abstract: The water allocations in the Amu Darya Basin reflect the colonial legacy of the Soviet Union: the downstream riparian states, Turkmenistan and Uzbekistan, were utilized to produce cotton while upstream Tajikistan used water for energy production and it was anticipated to increase its reservoir capacity further to provide water storage and facilitate agricultural production downstream, Afghanistan and Kyrgyzstan were considered simple producers of water without having a real claim to it. Independence manifested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…The dam will provide upstream Tajikistan with hydropower, while the downstream countries fear that it could negatively impact their irrigated agriculture [99,110]. In addition, tensions between Uzbekistan and Turkmenistan are not uncommon as the water storage infrastructure providing water to Uzbekistan is located in Turkmenistan [100,111]. These countries have considered switching from cotton to wheat production for food self-sufficiency, which could lead to water savings if the irrigation systems were efficient [111].…”
Section: Water-energy-food Security Nexus Issues In Camentioning
confidence: 99%
See 1 more Smart Citation
“…The dam will provide upstream Tajikistan with hydropower, while the downstream countries fear that it could negatively impact their irrigated agriculture [99,110]. In addition, tensions between Uzbekistan and Turkmenistan are not uncommon as the water storage infrastructure providing water to Uzbekistan is located in Turkmenistan [100,111]. These countries have considered switching from cotton to wheat production for food self-sufficiency, which could lead to water savings if the irrigation systems were efficient [111].…”
Section: Water-energy-food Security Nexus Issues In Camentioning
confidence: 99%
“…In addition, tensions between Uzbekistan and Turkmenistan are not uncommon as the water storage infrastructure providing water to Uzbekistan is located in Turkmenistan [100,111]. These countries have considered switching from cotton to wheat production for food self-sufficiency, which could lead to water savings if the irrigation systems were efficient [111]. Wegerich [111] demonstrated that, given the current situation, the riparian states of Turkmenistan, Tajikistan, and Uzbekistan will follow the strategy of resource capture, without consideration of the water requirements of neighboring countries.…”
Section: Water-energy-food Security Nexus Issues In Camentioning
confidence: 99%
“…Water 2016, 8,193 6 of 28 cotton) and provided fossil fuel for heating, while upstream states stored water to facilitate agricultural production downstream as well as to produce hydropower energy [26,67]. The Amu Darya and Syr Darya Rivers were seen as resources to be utilised to allow development, in what has been described as a "hydraulic mission" [68].…”
Section: Central Asiamentioning
confidence: 99%
“…Unsustainably high water use, particularly for irrigation, has led to high water stress and resulting environmental consequences, most visibly on the Aral Sea [27,[69][70][71][72]. Today, key aspects and challenges of the nexus in Central Asia are linked to the historic infrastructural interdependences via water storages, dams and power grids, and high profile competition over the water resources [26][27][28]67] (Figure 3). After becoming independent, the Central Asian countries were left in a state of high level interdependency with the individual states increasing their focus on national interests [26].…”
Section: Central Asiamentioning
confidence: 99%
See 1 more Smart Citation